Bisexual, pansexual, queer: Non-binary identities and the sexual borderlands - Callis, April Scarlette (Sexualities, 2014)
This article focuses on sexualities in the USA that exist within the border between heterosexuality and homosexuality. I first examine the usefulness of applying borderland theory to non-gay/non-straight sexualities such as queer and bisexual. I then give an ethnographic analysis of sexual self-identities on the borders, shedding light on how participants envisioned labels such as ‘pansexual,’ and ‘heteroflexible.’ Finally, I explore the ways that the sexual borderlands became tangible in Lexington, Kentucky at certain events and locations. Throughout, I highlight the ways that the sexual borderland touches on all sexualities, as individuals knowingly cross, inhabit, or bolster sexual identity borders.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; LGBTQIA2+; amériques; anthropologie; approches et analyses; discipline; identités LGBTQIA2+; périodes historiques; queer; ressource en ligne; régions géographiques; sciences humaines; sexologie; sexualité; thématiques; états-unis; étude qualitative

How they got it and how they wanted it: Marginalised young people's perspective on their experiences of sexual health education - Brown, Graham; Sorenson, Anne; Hildebrand, Janina (Sex Education, 2012)
Young people in Australia are at greatest risk of contracting sexually transmitted infections, and priority actions are necessary for this population group. This study of marginalised and at-risk young people in out-of-school environments was conducted in Western Australia with the aim of obtaining young people's perceptions about their experience of sexual health education and preferred means of gaining sexual health knowledge and skills. A participatory research methodology was implemented through a series of workshops with 88 young people recruited through community youth agencies. The results of the study support what is already known about sexual health promotion for young people and the importance of a holistic approach to promoting positive relationships and sexual health. However, the findings emphasise that this should include the need for demonstrated trust, confidence and safe environments, and the complementary role of community youth agencies and peer-based programmes which may play an important role in reaching young people who may disengage with, or not be reached by school-based sexual health education.
Keywords: 2000 à aujourd'hui; 2000-2009; adolescentes*; australie; discipline; personnes marginalisées; périodes historiques; recherche participative; ressource en ligne; régions géographiques; santé; santé sexuelle; sciences humaines; sexologie; sexualité; thématiques; éducation sexuelle

Identification des besoins de formation des enseignantes et des enseignants du secondaire en matière d'éducation à la sexualité dans le contexte de la réforme de l'éducation - Beaulieu, Nadine (Université du Québec à Rimouski, 2010)
L'objectif de cette étude est d'identifier les besoins de formation des enseignantes et des enseignants du secondaire en matière d'éducation à la sexualité en lien avec le contexte du renouveau pédagogique. Pour ce faire, nous avons élaboré et validé un questionnaire d'enquête de 36 questions que nous avons fait passer à 78 participants, tous enseignants au secondaire sur le territoire d'une commission scolaire du Bas-St-Laurent. Nos objectifs spécifiques sont plus précisément: 1) d'évaluer le niveau d'importance accordé par l'enseignant à chacune des six thématiques proposées par le MEQ et le MSSS en regard du mandat d'éducation à la sexualité auprès d'élèves de niveau secondaire; 2) d'évaluer le niveau de connaissances perçu de la part de l'enseignant en regard de la démarche d'éducation à la sexualité réalisée auprès d'élèves de niveau secondaire; 3) d'évaluer le niveau d'aisance perçu de la part de l'enseignant à aborder chacune de ces thématiques en regard de la démarche d'éducation à la sexualité réalisée auprès d'élèves de niveau secondaire; 4) d'identifier les liens possibles entre les différentes variables à l'étude. Les résultats de cette recherche démontrent que les participants reconnaissent l'importance d'une démarche d'éducation à la sexualité en milieu scolaire. Nous remarquons néanmoins que plus un enseignant avance en âge et moins il accorde de l'importance à l'éducation à la sexualité. De plus, les enseignants disent avoir un niveau de connaissances et d'aisance «satisfaisant» pour aborder les différentes thématiques suggérées par le MEQ-MSSS (2003). Par ailleurs, nous constatons une différence en ce qui a trait à la thématique «violence sexuelle» puisqu'elle est celle pour laquelle les participants accordent le plus d'importance, mais représente aussi celle pour laquelle ils disent en connaître le moins et être le moins à l'aise. Également, il apparaît que plus un enseignant accorde un niveau d'importance élevé à une thématique, plus ce dernier dit avoir un niveau élevé de connaissances et d'aisance. En conclusion, nous ferons état des pistes de réflexion quant à la formation des enseignants en matière d'éducation à la sexualité à l'intention des universités québécoises dispensant un baccalauréat en enseignement au secondaire (BES) ainsi qu'aux décideurs.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; discipline; mémoires/thèses; périodes historiques; québec; ressource en ligne; régions géographiques; santé; santé sexuelle; sciences humaines; sexologie; sexualité; stéréotypes de genre; thématiques; violences; violences sexuelles; éducation sexuelle; étude quantitative

Young men, masculinities and sex education - Limmer, Mark (Sex Education : Sexuality, Society and Learning, 2010)
This paper draws on focus group and interview data from 45 young men from the north of England to explore the barriers to effective sex and relationships education (SRE). Recent policy debates in relation to establishing statutory SRE in schools provide an opportunity to revisit how it is currently delivered to, and received by, young men. The paper considers the central role played by masculinities and how this role is mediated by social exclusion and poor engagement; it is suggested that addressing masculinities directly should be a priority for future SRE. In conclusion, some tentative approaches to addressing the issues are suggested.
Keywords: 2000 à aujourd'hui; 2000-2009; angleterre; discipline; europe; hommes*; jeunes adultes; masculinité; périodes historiques; régions géographiques; santé; santé sexuelle; sciences humaines; sexologie; sexualité; thématiques; éducation sexuelle